Penerapan Metode Waspas Untuk Efektifitas Pengambilan Keputusan Pemutusan Hubungan Kerja - Daulay, Nelly Khairani (Jurnal Sistem Komputer dan Informatika (JSON), 2021)
Layoffs are the most feared thing for every employee. There are many reasons behind a termination. For example, the company is experiencing a decline in terms of revenue so it feels necessary for a reduction in employees. Then the mistakes made by the employee itself such as criminal acts or mistakes in the work, or perhaps the personal desire of the employee himself due to personal reasons. But in the event of termination of employment, the leadership should be wise so as not to happen things that can interfere with the sustainability of the company. Because often the assessment given to employees is not subjective so it harms the employee itself. To overcome this, a decision support system is needed that can help the leadership to be able to take good policies. This decision-making system (SPK) requires a method in the process of completion. There are many methods that can be used one of them is the WASPAS method. The purpose of this research is to give an overview to the leadership in order to make good decisions so as not to harm employees. The results obtained by Karywan with the smallest value will be laid off. The smallest value is obtained by employee no. 4 with a value of 0.75